Flooding events reshape bacterioplankton assemblages and functional properties in a hypertrophic Shallow Lake (Laguna Chascomús, Argentina) - Patricia Yong Macias; Marcela Ferraro; José Fernando Bustingorry; Roberto Escaray; María de los Ángeles González Sagrario; María E. Llames (Hydrobiologia, 2026)

Phenotypic plasticity in freshwater picocyanobacteria - Paula Huber; Nadia Diovisalvi; Marcela Ferraro; Sebastián Metz; Leonardo Lagomarsino; María Eugenia Llames; Marta Royo‐Llonch; José Bustingorry; Roberto Escaray; Silvia G. Acinas; Josep M. Gasol; Fernando Unrein (Environmental Microbiology, 2017)
Summary Picocyanobacteria can occur as single‐cell (Pcy) or as colonies (CPcy). Published evidence suggests that some Pcy strains have the capability to aggregate under certain culture conditions, however this has not been demonstrated to occur in natural environments. We investigated whether the Pcy and CPcy belong to the same species (i.e. phylotype), and the factors that determine their morphological and genetic variability in a hypertrophic shallow lake dominated by picocyanobacteria. Six main different morphologies and >30 phylotypes were observed. All sequences retrieved belonged to the ‘ Anathece + Cyanobium ’ clade (Synechococcales) that are known to have the capability of aggregation/disaggregation. The temporal variation of picocyanobacteria morphotype composition was weakly correlated with the DGGE temporal pattern, and could be explained by the composition of the zooplankton assemblage. Laboratory experiments confirmed that the small cladoceran Bosmina favoured the dominance of CPcy, i.e. Cyanodictyon doubled the size of the colonies when present, most likely through the aggregation of single‐cell picocyanobacteria into colonies. Flow cytometry cell sorting and 16S rRNA + ITS sequencing of the Pcy and CPcy cytometrically‐defined populations revealed that some phylotypes could be found in both sorted populations, suggesting phenotypic plasticity in which various Synechococcales phylotypes could be found in situ either as single‐cells or as colonies.

New evidences of Roundup® (glyphosate formulation) impact on the periphyton community and the water quality of freshwater ecosystems - María S. Vera; Leonardo Lagomarsino; Matías Sylvester; Gonzalo L. Pérez; Patricia Rodríguez; Hernán Mugni; Rodrigo Sinistro; Marcela Ferraro; Carlos Bonetto; Horacio Zagarese; Haydée Pizarro (Ecotoxicology, 2010)

Ultraviolet damage and counteracting mechanisms in the freshwater copepod Boeckella poppei from the Antarctic Peninsula - Vanina E. Rocco; Oscar Oppezzo; Ramón Pizarro; Ruben Sommaruga; Marcela Ferraro; Horacio E. Zagarese (Limnology and Oceanography, 2002)
The process of ozone depletion over the Antarctic continent has resulted in the increase of incident ultraviolet‐B (UVB) radiation, whose effects may be damaging to living organisms. To counteract the negative effects of ultraviolet radiation (UVR), aquatic organisms may display one or more strategies: (1) avoidance (i.e. deep distribution); (2) photoprotection through the use of “sunscreen” compounds, such as mycosporine‐like amino acids (MAAs); and (3) enzymatic repair of the damage. The effects of UVR were assessed on four populations of the copepod Boeckella poppei from Antarctic lakes using laboratory and field experiments. The results were related to measurements of DNA enzymatic repair activity and MAA concentration. This is the first study that combines these measurements in zooplankton. Boeckella poppei was highly tolerant to UVR (LD 50 = 2.2–2.78 J cm −2 ). However, measurements of photorecovery (comparison of UVB mortality in the presence and absence of photoreactivating light) and dosage of photolyase activity indicated low rates of enzymatic repair, which may be the result of low temperatures typical of Antarctic lakes. Three different MAAs were identified, both in phytoplankton and copepods: porphyra‐334, mycosporine‐glycine, and shinorine. The population of B. poppei from Lake Boeckella had the lowest MAA concentration, as well as the lowest tolerance to artificial and natural UVR. These findings support the idea that UV tolerance in this species is related to the accumulation of MAAs. A comparison of the strategies used to cope with potentially damaging levels of UVR by different species of Boeckella indicates a high degree of plasticity in this genus, which has probably been key for its success to colonize a wide range of UV environments.